“Scalds of America”. Bayard Taylor and Samuel Kneeland in the Millennium of the Colonisation of Iceland (1874) - Mossé, Marie (Viatica, 2017)
International audience In the Romantic period, Travel mixed writing about elsewhere with writing about oneself. The naturalist Samuel Kneeland and the poet and journalist Bayard Taylor, travelling to Iceland in 1874, took advantage of this new plasticity offered by travel writing. The two Americans composed a unique literary relationship in which scholarly discourse faded away to give way to an imaginative relationship with reality.